Web based Real Time Water Pressure Monitoring System - A. Ejah Umraeni Salam; Muh .; Tola .; Mary Selintung; Farouk Maricar (Proceeding of the Electrical Engineering Computer Science and Informatics, 2014)
Nowadays, researches on real-time monitoring system have developed greatly. This research is intended to develop a real-time water pressure monitoring system on water distribution networks. Pressure monitoring is very important in assuring the availability of water supply to the community. Therefore, it is reasonable to develop a web-based real-time water monitoring system which is more efficient and easier to use.This system utilized MPX5700AP as sensor to measure water pressure and Arduino UNO as system’s performance control center with GSM/GPRS Shield application enabling the system to communicate with the server through GSM/GPRS network. This system was designed by applying C Arduino, HTML, PHP, and SQL as programming languages.Result of the evaluations indicated system prototype operated well. System was able to measure water pressure and displaying graphics and data of the measurement on the webpage.